2019
DOI: 10.1038/s41598-019-52765-7
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin mediates inhibition of exosome synthesis, localization and secretion via multicomponent interventions

Abstract: Discovery of exosomes as modulator of cellular communication has added a new dimension to our understanding of biological processes. Exosomes influence the biological systems by mediating trans-communication across tissues and cells, which has important implication for health and disease. In absence of well-characterized modulators of exosome biogenesis, an alternative option is to target pathways generating important exosomal components. Cholesterol represents one such essential component required for exosoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 28 publications
(30 reference statements)
1
38
0
Order By: Relevance
“…Simvastatin, which is often used to decrease elevated lipid levels and the risk of heart problems in those at high risk, also exhibited the ability to inhibit the secretion of exosome 51 . Data showed that epithelial cells and monocytes treated with different concentrations of simvastatin for 24 h exhibited a significant reduction in the level of secreted exosomes, and a significant reduction of about 40% was noted at the 0.3 µM dose of simvastatin, so its exosome inhibitory effect was significant.…”
Section: Exosome Inhibitorsmentioning
confidence: 99%
“…Simvastatin, which is often used to decrease elevated lipid levels and the risk of heart problems in those at high risk, also exhibited the ability to inhibit the secretion of exosome 51 . Data showed that epithelial cells and monocytes treated with different concentrations of simvastatin for 24 h exhibited a significant reduction in the level of secreted exosomes, and a significant reduction of about 40% was noted at the 0.3 µM dose of simvastatin, so its exosome inhibitory effect was significant.…”
Section: Exosome Inhibitorsmentioning
confidence: 99%
“…Last, simvastatin was recently identified as an inhibitor of EV secretion based on the rationale that cholesterol is necessary for the formation of vesicle membranes. However, simvastatin's function as an HMG-CoA reductase inhibitor does not entirely explain the mechanism, as supplementation with mevalonate did not fully restore EV output to baseline levels (111). Given that different mechanisms of EV biogenesis exist, we may utilize this knowledge to selectively target (inhibit) specific populations of EVs while leaving other subsets of EVs untouched.…”
Section: Modulating Ev Secretion As a Mechanism To Control Cytokine Rmentioning
confidence: 99%
“…Modulating exosome release appears to be an attractive therapeutic intervention ( McAndrews and Kalluri, 2019 ), especially in immuno-oncology because of the critical roles of exosomes in tumor progression and immune evasion ( Hoshino et al, 2015 ; Chen et al, 2018 ; Poggio et al, 2019 ; Wortzel et al, 2019 ; Daassi et al, 2020 ). Despite various drug discovery attempts from empirical study to drug repurposing and high throughput screening ( Trajkovic et al, 2008 ; Chalmin et al, 2010 ; Ostrowski et al, 2010 ; Datta et al, 2018 ; Kosgodage et al, 2018 ; Im et al, 2019 ; Kulshreshtha et al, 2019 ), targeting exosomes for the treatment of disease has been challenging due to exosome’s complex biogenesis, dynamic contents, heterogeneous origins, and diverse functions ( Jeppesen et al, 2019 ; Pegtel and Gould, 2019 ; Kalluri and LeBleu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%